A step toward reducing air pollution in top Asian economies: The role of green energy, eco-innovation, and environmental taxes. (1st November 2021) - Chien, Fengsheng; Sadiq, Muhammad; Nawaz, Muhammad Atif; Hussain, Muhammed Sajjad; Tran, Tai Duc; Le Thanh, Tiep
Abstract: Environmental degradation is significantly studied both in the past and the current literature; however, steps towards reducing the environmental pollution in carbon emission and haze pollution like PM2.5 are not under rational attention. This study tries to cover this gap while considering the carbon emission and PM2.5 through observing the role of renewable energy, non-renewable energy, environmental taxes, and ecological innovation for the top Asian economies from 1990 to 2017. For analysis purposes, this research considers cross-sectional dependence analysis, unit root test with and without structural break (Pesaran, 2007), slope heterogeneity analysis, Westerlund and Edgerton (2008) panel cointegration analysis, Banerjee and Carrion-i-Silvestre (2017) cointegration analysis, long-short run CS-ARDL results, as well as AMG and CCEMG for robustness check. The empirical evidence in both the short- and long-run has confirmed the negative and significant effect of renewable energy sources, ecological innovation, and environmental taxes on carbon emissions and PM2.5. Whereas, non-renewable energy sources are causing environmental degradation in the targeted economies. Finally, various policy implications related to carbon emission and haze pollution like PM2.5 are also provided to control their harmful effect on the natural environment. Highlights: Renewable energy sources, ecological innovation, and environmental taxes negatively effect on carbon emissions and PM2.5. Non-renewable energy sources are causing environmental degradation in the form of carbon emission. Renewable energy sources reduce the higher level of carbon emissions in the targeted economies. Renewable energy, ecological innovation, and environmental taxes positively impacted the environment in Asian countries.